Implementasi pendidikan seks pada santri di pondok pesantren - Hasanah, Nur; Asdiqoh, Siti; Famularsih, Sari (Nur Science Institute, 2025)
Sexuality education is a process of providing information and understanding about the body, relationships, sex, gender, and reproductive health. Its purpose is not merely to inform about sex, but to help individuals make healthy, safe, and responsible decisions. This study aims to: (1) examine the implementation of sexuality education for students (santri) in Islamic boarding schools (pesantren), and (2) identify the challenges and solutions in its implementation. The research employed observation, interviews, and documentation as data collection methods. The findings reveal that sexuality education at Pondok Pesantren Al Bahroniyyah in Demak and Pondok Pesantren Al Manar in Tengaran is carried out in stages, beginning when students reach puberty (baligh). Preparatory classes are provided, including instruction in language and Islamic jurisprudence (fiqh), as well as guidance on social interaction ethics. As a solution to overcome implementation barriers, both pesantren enforce written rules that all students must follow. These rules are posted in strategic locations such as the hall, dormitory rooms, and classrooms. Any violation of these regulations results in sanctions, adjusted according to the severity of the offence.